Regulation of the human histamine H1 receptor stably expressed in Chinese hamster ovary cells. - Smit, M. J. (1996)
1. The human H1 receptor gene expressed in Chinese hamster ovary cells (CHOhumH1) encodes a classical histamine H1 receptor with a pharmacology similar to that of the H1 receptor found in guinea-pig cerebellum and the endogenously expressed human H1 receptor in 1321N1 astrocytoma cells as determined by [3H]-mepyramine binding studies. 2. In CHOhumH1 cells, histamine induced a concentration-dependent rise in inositol phosphates (EC50 2.23 +/- 0.97 microM) and a rapid increase of [Ca2+]i, followed by a sustained increase of [Ca2+]i upon addition of 100 microM histamine. 3. Short-term exposure of CHOhumH1 cells to histamine (100 microM) resulted in a decrease of subsequent histamine-induced Ca2+ responses. The histamine-induced desensitization appeared to be heterologous as the ATP-induced Ca2+ response was also found to be affected. 4. The process of heterologous histamine-induced desensitization of the Ca2+ response in CHOhumH1 cells can be ascribed to an alteration at the level of the intracellular Ca2+ pool, as the Ca2+ response of caffeine (10 mM), which releases Ca2+ from intracellular Ca2+ stores was also attenuated upon short-term histamine exposure. 5. In CHOhumH1 cells the PKC activator, PMA, was found to inhibit the histamine (100 microM)-induced Ca2+ response concentration-dependently (IC50 0.2 +/- 0.03 microM) as well as the ATP (100 microM)-induced Ca2+ response. However, this inhibition was only partial and less effective than histamine-pretreatment. Moreover, in CHOhumH1 cells PKC downregulation induced by long-term exposure to PMA (1 microM) did not affect the histamine-induced desensitization nor did pretreatment with the specific PKC inhibitor Ro-31-8220 (10 microM), indicating that in CHOhumH1 cells PKC is probably not involved in the heterologous desensitization. 6. Long-term treatment of CHOhumH1 cells with histamine or other H1 agonists resulted in a time- and concentration-dependent decrease in the number of H1 receptor binding sites (maximal reduction: 47 +/- 5%). 7. Long-term exposure of CHOhumH1 cells to ATP or PMA did not affect H1 receptor density. 8. Both histamine (100 microM)- and ATP (100 microM)-induced Ca2+ responses were affected upon long-term exposure of cells to histamine (100 microM), which might be explained by an alteration at a level distant from the receptor. 9. These results show that in CHOhumH1 cells the human histamine H1 receptor is susceptible to short-term and long-term receptor regulation in which PKC does not seem to play a role. The CHOhumH1 cells therefore provide an excellent model system for studying the mechanism(s) of PKC-independent H1 receptor regulation.